Effect of sugar beet mixed feed for fattening of Jinding male duck available in Khulna, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
This study was aimed to economic evaluation of using of sugar beet for fattening Jinding duck. A total number of 160, male one day old, Jinding ducklings were used in this study. All ducks were weighed individually and distributed randomly among 4 treatments, each treatment includes 40 ducklings were nearly similar in initial average body weights and each treatment was 4 blocks of 13 ducklings. Chemical analysis for rations was applied and different productive and economic measures applied. The results showed significant differences (p>0.05) among all groups for the final body weight where the control groups it was 389.40±251.87 gram and for T2, T3, and T4 the final body weight were 641.93±503.98, 693.55±500.33, 693.55±500.33 respectively. And also there were significant differences (p< 0.05) among all groups for the total feed intake were at the control groups it was 903.83±467.34 and for the T2, T3, and T4 for the total feed intake were 792.70±483.25, 845.60±471.20 and 833.98±465.28 gram respectively. The feed conversion rate showed significant difference (p